The Relationship Between Neopterin Levels and Cardiac Troponin in Patients with Non-St Segment Elevation Acute Coronary Syndromes - Yazıcı, M.; Durna, K.; Demircan, S.; Gülel, O.; Şahin, M. (My University, 2007)
Objectives: We examined the relationship between neopterin level, a locally and specific marker of inflammation, and cardiac troponin release in patients with non-ST elevation acute coronary syndromes (NSTE-ACS). Study design: The study included 234 patients with NSTE-ACS and angiographically documented coronary artery disease. Serum levels of neopterin and cardiac troponin-I (cTn-I) were measured on admission. The patients were analyzed in two groups: 137 patients were cTn-I negative (<0.2 ng/ml), 97 patients were cTn-I positive (≥0.2 ng/ml). The presence of thrombus, lesion morphology, and TIMI flow were examined by coronary angiography. Results: The two groups did not differ significantly with regard to the localization of culprit lesions and lesion morphology. The presence of TIMI ≤2 flow was significantly higher in cTn-I positive patients (p<0.001). The rates of visible thrombi during coronary angiography were 24.7% and 7.3% in cTn-I positive and negative patients, respectively (p=0.012). Serum neopterin levels were higher in cTn-I positive patients (p<0.001) and were correlated with cTn-I levels (r=0.817, p<0.001). In logistic regression analysis, neopterin was found as the only independent factor affecting cTn-I positivity (Odds ratio=1.4; p<0.001). ROC analysis showed 12.55 nmol as the optimal cutoff for neopterin level. The rates of sensitivity, specificity, positive predictive value, and negative predictive value for neopterin in distinguishing cTn-I positive and negative patients were 65.9%, 64.2%, 56.2%, and 72.1%, respectively. Conclusion: Our results demonstrate that higher cTn-I levels may be related with neopterin levels, which reflect local inflammatory activity in patients with NSTE-ACS.
ST Yükselmesi Olmayan Akut Koroner Sendromlarda Neopterin Düzeylerinin Kardiyak Troponinle İlişkisi
Keywords: Angina; Coronary Angiography; Coronary Disease; Coronary Thrombosis; Neopterin/Blood; Troponin I/Blood; Unstable